Efektivitas Terapi Nebulizer terhadap Bersihan Jalan Napas Anak dengan Bronkopneumonia - Legal Bagas Perdana; Etika Dewi Cahyaningrum (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Bronchopneumonia is the most common form of pneumonia in children and remains a leading cause of death in those under five years of age. This condition is characterized by shortness of breath due to lung infection. One of the interventions used is nebulizer inhalation therapy, which helps relieve breathing difficulties and thin secretions. This study aims to evaluate the effectiveness of inhalation therapy in children experiencing ineffective airway clearance. The method applied is a case study based on evidence-based practice (EBP) involving one patient, with nebulizer interventions administered for three consecutive days, each lasting 10–15 minutes. The findings showed improvement, including reduced shortness of breath, decreased productive cough, and the disappearance of rhonchi. Therefore, nebulizer therapy is proven effective in managing respiratory problems in children with bronchopneumonia, and its implementation should be accompanied by education for patients and their families to support collaborative nursing care.